Evaluación y perspectivas del programa Pro-Árbol en México 2007-2012 - Pérez Medrano, Roberto (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The Pro-Írbol program became the main campaign strategy of President Felipe Calderón Hinojosa to drive planning and sustainable forestry development in Mexico, which is instrument and took place in the period 2007-2012, with the main base Strategic Forestry Program (PEF) 2025, the National Development Plan (PLANADE), which emphasizes on the implementation of public policies to ensure sustainable human development, Environment Sector Program (PSMA) that favors sustainable development of forestry and their associated resources and Decentralized Public Agency of the Ministry of Environment and Natural resources (SEMARNAT), responsible for the execution of the work program referred to derivatives (PIF) Institutional Forestry program of the National Forestry Commission (CONAFOR). It is crucial to note that for the first time in the history of our country, a significant and comparable to first world countries for the implementation of Pro-Írbol assigned program budget; which in principle was integrated into 44 components clustered into different categories of support: forest planning and organization, production and productivity, conservation and restoration and raise competitiveness. However, apparently the allocation and application of the resources of the program in question was not performed with the efficiency required to ensure compliance with the objectives and goals set; for this reason in the present research, the assessment of consistency and results of 7 most representative components of the Pro-Tree was made using a rule, the Logical Framework Methodology (MML) also were made a number of surveys among different stakeholders: producers, providers of technical assistance and technical groups and environmentalists CONAFOR officials, for their views on the degree of effectiveness of the program.

El programa Pro-árbol, se constituyó en la estrategia principal de campaña del presidente Felipe Calderón Hinojosa para impulsar la planeación y el desarrollo forestal sustentable en México, misma que se instrumentó y llevo a cabo en el periodo 2007-2012, teniendo como base principal el Programa Estratégico Forestal (PEF) 2025, el Plan Nacional de Desarrollo (PLANADE), que enfatiza sobre la implementación de políticas públicas que garanticen el desarrollo humano sustentable, el Programa Sectorial de Medio Ambiente (PSMA) que privilegia el desarrollo sustentable del sector forestal y sus recursos asociados y el Programa Institucional Forestal (PIF) de la Comisión Nacional Forestal (CONAFOR), Organismo Público Descentralizado de la Secretaria de Medio Ambiente y recursos Naturales (SEMARNAT), responsable de la ejecución de los trabajos derivados del programa referido. Resulta trascendental destacar que por primera vez en la historia de nuestro país, se asignó un presupuesto importante y equiparable al de los países de primer mundo para la ejecución del programa Pro-árbol; el cual en principio, fue integrado en 44 diferentes componentes aglutinados en las categorías de apoyo: planeación y organización forestal, producción y productividad, conservación y restauración y elevar los niveles de competitividad. No obstante, aparentemente la asignación y aplicación de los recursos económicos del programa en cuestión, no se realizó con la eficiencia requerida para asegurar el cumplimiento de los objetivos y metas programadas; por tal razón en el presente trabajo de investigación, se realizó la evaluación de consistencia y resultados de 6 de los componentes de mayor representatividad del Pro-Árbol, utilizando por norma, la Metodología del Marco Lógico (MML), asimismo se efectuaron una serie de encuestas entre los diferentes involucrados: productores, prestadores de asistencia técnica grupos ecologistas y técnicos y funcionarios de la CONAFOR, para conocer su opinión sobre el grado de efectividad del programa.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Políticas Públicas
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2014-1415; Pro-árbol; CONAFOR; SEMARNAT; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/983